DILEMMA OF THE «SOFT» AND «HARD» FORCE: THE LESSONS OF THE UKRAINIAN CRISIS - M. A. Neimark (Проблемы постсоветского пространства, 2017)
The article reveals the key particularities of the “soft” and “hard power” in the context of the “smart leadership” strategy in the world politics. This text examines the different aspects of the concept of “soft power”, its practical problems, and particularities of the public diplomacy, the limits and perspectives of “soft power” in the light of the internationalization of the Ukrainian crisis.